Optimalisasi Penegakan Diagnosis Keperawatan Sesuai Standar Asuhan Keperawatan di Rumah Sakit X - Mu'minah Mu'minah; Tuti Afriani; Krisna Yetti; Dudi Mashudi; Khairul Nasri (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the enforcement of nursing diagnoses according to the Nursing Care Standards of X Hospital Jakarta. The research method uses a case study approach with interviews, document review and observation, and performs problem analysis using fishbone analysis. The results showed that the enforcement of nursing diagnoses in accordance with the Standards of Nursing Care was not optimal, so that it had an impact on the quality of care and its documentation. Nursing diagnoses that are in accordance with Nursing Care Standards are 48.6%. Lack of supervision from managers, assessments using personal assumptions and the standard of writing diagnoses in the local Hospital Information System (SIRS) has not been facilitated. Through strengthening the directing function with SAK media innovation, there was an increase in writing nursing diagnoses according to SAK to 62.3%. In conclusion, optimizing the enforcement of nursing diagnoses in accordance with Nursing Care Standards can be implemented with SAK media innovations (Softfiles on the Google Form Platform and flipcharts) which are given to implementing nurses at X Hospital. Keywords: Diagnosis, Nursing Documentation, Quality, Nursing Care Standards